2021
DOI: 10.3892/etm.2021.10671
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein phosphatase 2A in kidney disease (Review)

Abstract: Kidney disease affects millions of people worldwide and is a financial burden on the healthcare system. Protein phosphatase 2A (PP2A), which is involved in renal development and the function of ion-transport proteins, aquaporin-2 and podocytes, is likely to serve an important role in renal processes. PP2A is associated with the pathogenesis of a variety of different kidney diseases including podocyte injury, inflammation, tumors and chronic kidney disease. The current review aimed to discuss the structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 126 publications
0
10
0
Order By: Relevance
“…Various studies demonstrated that the physiological role of POP is to regulate PP2A; particularly, POP inhibition was recently shown to increase PP2A activity, thereby reducing oxidative stress [ 39 , 40 ]. Moreover, PP2A serves an important role in protection against renal inflammation [ 41 ]. To demonstrate whether PP2A is also activated (i.e., dephosphorylated) by KYP2047 during KI/R, the activated form of PP2A, and the inactivated form (pPP2A) were measured in kidney samples, showing as KYP2047 treatment significantly increased PP2A and reduced pPP2A (respectively, Figure 8 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies demonstrated that the physiological role of POP is to regulate PP2A; particularly, POP inhibition was recently shown to increase PP2A activity, thereby reducing oxidative stress [ 39 , 40 ]. Moreover, PP2A serves an important role in protection against renal inflammation [ 41 ]. To demonstrate whether PP2A is also activated (i.e., dephosphorylated) by KYP2047 during KI/R, the activated form of PP2A, and the inactivated form (pPP2A) were measured in kidney samples, showing as KYP2047 treatment significantly increased PP2A and reduced pPP2A (respectively, Figure 8 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that PP2A serves an important role in protection against renal inflammation [ 41 ] and the developmental regulation of PP2A activity and protein during kidney growth suggests a role for PP2A in the regulation of nephron differentiation [ 66 ]. For the first time, in this study, the involvement of PP2A was demonstrated in renal ischemia/reperfusion injury, suggesting an important connection between POP-inhibition and PP2A activity, and strengthening the anti-inflammatory mechanisms of KYP2047 treatment through PP2A activation.…”
Section: Discussionmentioning
confidence: 99%
“…This heightened expression of PP2Ac in patients with SLE plays a substantial anti-inflammatory role in renal tissues 26 and is also found to enhance the stability of podocytes. 27 This increased serum level of PP2A regulatory subunit (IGBP1) in LN may contribute to understanding the histological podocyte injury observed in various LN classes. 28,29 Unlike the most severe classes of LN (classes III and IV) that are associated with anti-dsDNA antibodies that induce complement activation and inflammatory reactions, 30 membranous LN (class V) is characterized by subepithelial deposits, leading to local complement activation and more pronounced podocyte dysfunction, typically with little or no inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of these processes is likely to have major functional implications since TJs and epithelial polarity play a critical role in kidney homeostasis, and the kidney is an important site for one-carbon metabolism ( Ducker and Rabinowitz, 2017 ). Indeed, disturbances in one-carbon metabolism ( Karmin and Siow, 2018 ), deregulation of PP2A ( Shao et al, 2021 ) and TJ dysfunction ( Denker and Sabath, 2011 ; Szaszi and Amoozadeh, 2014 ; Bhat et al, 2018 ) are all linked to various kidney diseases, including carcinomas.…”
Section: Discussionmentioning
confidence: 99%